The Role of Students as Legal Assistants in Litigation Assistance Activities in the Community - Abdurrozaq, Muhammad Wafa; Mahendra, Hazlam Roy (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2023)
Students is an entity of agent of change. The role of students in carrying out legal assistance is one of service in the community, considering that students are agents of change. Legal, both written and unwritten, of course, is to bring justice in the body of society. The problem factor that is often an obstacle in the realization of justice in society is limitation or limited access to legal services, in this case lawyers or advocates due to economic factors and the factor of the public's grain of legal assistance. This must certainly be addressed to students as an agent of change who is able to bring change by becoming a legal assistant or legal companion in providing legal services to the community. If justice in society is realized, it will allow each layer of society to get the opportunity to develop its entire potential. Based on this, this article aims to review (1) How the role of students as Legal Assistants in community assistance activities; (2) What is expected from litigation assistance activities in the community from the perspective of students and the community. Where in relation, law students can participate in serving the community and have the opportunity to develop the potential they have in the field of law, as well as applying the knowledge they get during the classroom learning process.